Addiction Education and Training for Counselors: A Qualitative Study of Five Experts. Issue 2 (October 2014) - Lee, Tiffany K.
<x xml:space="preserve">Abstract</x> Five themes emerged based on interviews of faculty with addiction counseling expertise. The findings are relevant to practitioners, educators, and students. Recommendations for the counseling field are addressed, and suggestions for addiction content, course design, and pedagogy are included.